Standard methods for American foulbrood research - Graaf, Dirk C. de (2013)
American foulbrood is one of the most devastating diseases of the honey bee. It is caused by the spore-forming, Gram-positive rod-shaped bacterium Paenibacillus larvae. The recent updated genome assembly and annotation for this pathogen now permits in-depth molecular studies. In this paper, selected techniques and protocols for American foulbrood research are provided, mostly in a recipe-like format that permits easy implementation in the laboratory. Topics covered include: working with Paenibacillus larvae, basic microbiological techniques, experimental infection, and “’omics” and other sophisticated techniques. Further, this chapter covers other technical information including biosafety measures to guarantee the safe handling of this pathogen.